Alien Carousel: In Situ life detection on icy moons with a single-actuator holographic microfluidic platform - Meersman, M. F. L.; Cazaux, S. M.; Jovanova, J. (Frontiers in Astronomy and Space Sciences, 2025)
Enceladus, one of Saturn’s moons, is considered one of the most promising places in the solar system to find life. The Cassini mission discovered organic-rich water plumes from Enceladus’s subsurface ocean, prompting new lander mission planning. We developed a mechanically simple ice sampling system for autonomous life detection on lander missions. The system is controlled by a single rotary actuator that samples, liquefies, and prepares ice for microscopic observations. Sample acquisition uses a novel conical boundary layer pump that delivers samples to a microfluidic disk. A digital holographic microscope detects microorganisms without mechanical focusing. The single-actuator design enables closed-loop control of velocity, position, and torque, with an operational sequence controlling fluid dynamics in a centrifugal microfluidic disk. Testing demonstrated system feasibility and effectiveness across all subsystems. Open-source software was developed for automated onboard hologram processing, including organism motility detection to assess presence of life. This single-actuator design reduces mechanical complexity for lander missions. Future work focuses on adapting the technology for terrestrial applications and achieving required technology readiness levels for space deployment.